Non-Surgical Orthodontic Treatment Of False Prognathie İnferior Case With Unilateral Cleft Lip-Palate - Tamer Türk; Ayşe Gülşen (Galenos Yayinevi, 1999)
Retrusion of middle face, anterior and posterior cross bite, absence of teeth and crowding are major problems that may be observed in unilateral or bilateral cleft lip-palate patients. If the required treatment is not carried out during the growth period, the chance of obtaining satisfactory results is highly decreased. The aim of this case report was to present the results of an orthodontic-prosthetically treated unilateral (left side) cleft lip-palate patient. At the end of treatment the SNA angle increased due to stimulation of upper jaw growth, the SNB angle decreased due to posterior rotation of the lower jaw. These skeletal changes lead to an increase of the ANB angle. Skeletal changes and at the same time the anterior movement of upper incisors were effective for the correction of the anterior cross bite.